Educating Chinese Nurses About Rehabilitation Nursing: Findings From a Single Cohort Quantitative Pilot Project. Issue 4 (July 2017) - Mauk, Kristen L.; Li, Pei Ying; Jin, Huilu; Rogers, Julie; Scalzitti, Kristina
Abstract: Purpose: The purpose of this study was to present results of a pilot program to educate nurses in China about rehabilitation nursing. Design: A single cohort, pre- and posttest design with an educational intervention. Methods: A 3-day basic rehabilitation nursing education program was conducted in Shanghai and Hangzhou by a certified rehabilitation nurse specialist from the United States. The effect of the educational intervention was measured using pre- and posttests for six topic areas. Data were analyzed using descriptive statistics, correlations, and paired samples t tests. Findings: Paired samples t tests showed a significant improvement ( p < .01) as a result of the educational intervention on all three tests covering the six basic topics. Conclusions: The knowledge of the nurses on topics of basic rehabilitation nursing significantly increased as a result of the educational program. Clinical Relevance: Rehabilitation nurses interested in international travel and developing professional relationships with nurses in China can provide education to promote our specialty practice overseas.